A survey on traditional practices adopted for restraining camel in Rajasthan - RANJAN, RAKESH; TUTEJA, F C; KASHINATH, KASHINATH; PATIL, N V (The Indian Journal of Animal Sciences, 2017)
The present study aimed to document details about traditional practices adopted for restraining camel in Rajasthan. The information was collected by discussing villagers of the study area using the "Transect walks" method of the Participatory Rural Appraisal (PRA) technique from August 2014 to September 2015. The study revealed that restraining practices vary with age of the animal and purpose of restraining. Homemade rope halter is primarily used for restraining young camels, while use of nose-peg and nose-rings are common techniques used in adult animals. Tying fore or hind legs with rope is frequently used for restraining animals in standing or sitting position.